Implementasi Struktur Meander Line untuk Mereduksi Ukuran Butler Matrix 2 × 2 - Zulfi; Achmad Munir (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2021)
Butler matrix is a beamforming network that is commonly used in multibeam antennas because of its simple structure and high efficiency. However, the Butler matrix has relatively large dimensions. Meander line structure is a widely used approach to reduce the dimensions of various microwave devices. This paper describes the implementation of the meander line structure on a 2 × 2 Butler matrix to reduce dimensions. The method used is to apply a meander line structure to the through arm. The 2 × 2 Butler matrix with meander line structure is designed using FR4 epoxy dielectric material with dimensions of 17.9 mm × 36.4 mm to work at a 2.4 GHz resonant frequency. The measurement results show that the 2 × 2 Butler matrix with meander line structure has a reflection coefficient better than -10 dB from 1.88 GHz to 2.93 GHz (fractional bandwidth of 43.75%). The isolation of -6.15 dB, the transmission coefficients of -3.70 dB, and the phase difference between the output ports is 91.37o were achieved at the operating frequency of 2.4 GHz. The application of the meander line structure reduces the dimensions of the Butler matrix 2 × 2 by 34.54%.